Development of Echovirus 29 Cytopathology in RD Cell Line Might not Happen within 10 Days Post Inoculation (2017)
Classically in enterovirology, isolation in RD cell culture required inoculation and incubation for 14 days before any sample is declared negative for enteroviruses. To reduce the turn-around time for confirming suspected cases of poliomyelitis, in 2010, the required incubation period, post inoculation was reduced to 10days. In this study we set out to determine why an Echovirus 29 (E29) strain we isolated in 2016 showed no cytopathology on RDcell culture despite the fact that other members of the clade to which it belongs do so. We found that the problem was not the 2016 E29 strain but the new 10 days incubation algorithm. To be precise, the 2016 E29 strain did not show cytopathology in RD cell line within the recommended 10 days but replicated with evident cytopathology when allowed to stay in culture for 13 to 14 days. This shows that some samples declared negative for enteroviruses by the 10 days incubation algorithm might be false negatives that will eventually develop cytopathology if allowed to remain in incubation for 13 to 14 days. It is therefore encouraged that those particularly interested in Non-Polio Enteroviruses endeavour to maintain at least 14 days incubation in cell culture in a bid to accommodate the likes of E29 that might need 13-14 days to develop CPE especially when present at low titre.